2021
DOI: 10.36320/ajb/v13.i1.8140
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and risk factors of Trichomonas vaginalis among couples in Al-Hamza city-Iraq.

Abstract: Background: Trichomoniasis is a sexually transmitted disease. It is a public health risk factor. This disease associated with many sexual diseases and is likely to be a cause of infertility, abortion, and the birth of low-weight babies. The purpose of the study is to establish a database of parasite infection in the city, especially with no previous research on the rate of infection among men.  Materials and method: Two hundred forty serum samples were collected from 120 couples  between 18-43 years old, for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…According to Hamoud et al, 2021, study results revealed high HCMV IgG antibodies titers among study groups which raises a question about these increased levels of prolonged existence antibodies and their impact on pregnancy progression and the probability of recurrent activation of the virus during pregnancy. Study results reported that there was an increment in HCMV IgG titer in the controls and this may be due to the impaired immunity of the pregnant women and the possibility of virus reactivation in this situation since the controls in this study were of pregnant women [23]. The HCMV IgG avidity test is dependent on the sensitivity of the HCMV IgM testing since the rise in IgM titer may happen before the rise in IgG titer following the initial infection.…”
Section: Immunological Detection Of Cytomegalovirus By Elisamentioning
confidence: 69%
See 2 more Smart Citations
“…According to Hamoud et al, 2021, study results revealed high HCMV IgG antibodies titers among study groups which raises a question about these increased levels of prolonged existence antibodies and their impact on pregnancy progression and the probability of recurrent activation of the virus during pregnancy. Study results reported that there was an increment in HCMV IgG titer in the controls and this may be due to the impaired immunity of the pregnant women and the possibility of virus reactivation in this situation since the controls in this study were of pregnant women [23]. The HCMV IgG avidity test is dependent on the sensitivity of the HCMV IgM testing since the rise in IgM titer may happen before the rise in IgG titer following the initial infection.…”
Section: Immunological Detection Of Cytomegalovirus By Elisamentioning
confidence: 69%
“…In Babylon AL-Hajjar and Al-Mousawi, [21] southern Iraq, has a high seroprevalence of HCMV IgG antibodies (90%) [22]. In Najaf, Hamoud et al [23] discovered a relatively high HCMV seroprevalence (95.09%), with no discernible variations between women who experienced multiple miscarriages and those who experienced a normal pregnancy.…”
Section: Immunological Detection Of Cytomegalovirus By Elisamentioning
confidence: 99%
See 1 more Smart Citation